Beyond canonical inflammasomes: emerging pathways in IL-1-mediated autoinflammatory disease - Lukens, John R. (2014)
In recent years non-communicable chronic diseases that are potentiated by sterile inflammation have replaced infectious diseases as the major threat to human health. Sterile inflammation that results from aberrant tissue damage plays pivotal roles in the pathogenesis of numerous acute and chronic inflammatory diseases including atherosclerosis, type 2 diabetes, cancer, obesity, and multiple neurodegenerative diseases. The cellular events and molecular signaling pathways that govern sterile inflammation currently remain poorly defined, however emerging data suggest central roles for IL-1 in driving autoimmune and inflammatory disease pathogenesis. Improved characterization of the immunological pathways that contribute to sterile inflammation are desperately needed to develop effective therapeutics to treat these devastating diseases. In this review we discuss recent advances in our understanding of how IL-1 is regulated in response to tissue damage. In particular, we highlight recent studies that describe novel roles for conventional cell death molecules in the regulation of IL-1β production.